Dominasi Pembiayaan Murabahah di Koperasi Syariah: Analisis Berdasarkan Fatwa Dewan Syariah Nasional (DSN-MUI) - Moh. Asep Zakariya Ansori; Abdul Husenudin; Salsabila Nurapipah; Saevina, M. Erga Firmansyah; Rocky Bayu Kamajaya (As-Syirkah: Islamic Economic & Financial Journal, 2026)
Murabahah financing is one of the most common types of agreements used in Islamic financial institutions, including Islamic cooperatives. The dominant use of murabahah contracts indicates that this type of contract is considered easier to implement, has a relatively lower risk, and provides certainty of profit for cooperatives. This study aims to analyze the factors causing the dominance of murabahah financing at Koperasi Syariah Ummul Quro Al-Islami and to test its alignment with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 on Murabahah. A qualitative method with a case study approach was employed. Primary data were obtained through interviews with the cooperative, while secondary data came from DSN-MUI fatwas, books, and scientific journals. Results indicate that the dominance of murabahah is influenced by the ease of transaction mechanisms, relatively lower risk, profit margin certainty, and high member interest in fixed-installment schemes. The implementation at this cooperative is generally in accordance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, as demonstrated through price transparency, clear margins, and mutual consent in contract execution.